Implementasi Understanding by Design (UbD) sebagai Kerangka Kerja Kurikulum Merdeka di SMA Santo Thomas 1 Medan - Sihotang, Friska Ladista; Juraganda S, Chandra Saptanto; Panggabean, Ellis Mardiana; Situmorang, Adi Suarman (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe the implementation of Understanding by Design (UbD) as a framework for the Merdeka Curriculum at Santo Thomas 1 High School in Medan. This study uses a descriptive approach with a mixed qualitative and quantitative design. Research data were collected through interviews with teachers, observations of teaching and learning activities, analysis of teaching materials, and measurement of teachers' perceptions using a Likert scale questionnaire. Qualitative data were analysed through data reduction, data presentation, and conclusion drawing, while quantitative data were analysed descriptively to determine the categories of UbD implementation levels. The results showed that UbD implementation was in the good category, especially in the planning and formulation of learning outcomes stages. However, the learning implementation and assessment stages still needed improvement because they were not fully consistent with the backward design principle. Overall, UbD played an important role in strengthening the quality of learning planning in the Merdeka Curriculum, but further assistance was still needed to optimise its application in all stages of learning.